Audyt wewnętrzny wspomagający zarządzanie sektorem publicznym – główne problemy i propozycje usprawnień: Internal audit management suppor public sector – the main problems and suggestions for improvement - Waściński, Tadeusz; Sławińska, Joanna (Management and Administration Journal, 2021)
The study provides information of the changes in the role of internal audit and the problems associated with the services provided by the auditors of the public sector. In accordance with the Polish administration definition internal auditing is an independent and objective assurance, the aim of which is to support the minister in charge of branch of government administration or the head of the unit in achieving the goals and objectives through a systematic evaluation of the management control in branch of government administration or unit, and consulting activities. Among the most important criteria for the evaluation of management control are adequacy, effectiveness and efficiency. This definition makes the area of auditing more com pliant with the International Standards for the Professional Practice of Internal Auditing. Under these standards, internal audit supports the head of the unit in the performance of his management tasks through a systematic and disciplined approach to evaluate, inter alia, control, and through consulting activities. The study also presents the different types of audits, including the efficiency audit, also known as the performance audit or audit value for money. This type of audit is particularly important in view of the implementation of accountability mechanisms in the administration of the activities carried out by the units, measurement of the achievement of planned objectives, results obtained in relation to the resources involved. The aim of this study is to answer the following questions: What is the role of internal audit in the Polish public administration at present? What problems exist in audit activity? What are the solutions to be implemented in the public finance sector in order to improve the internal audit function? The above issues are dealt with on the basis of the literature and the results of research and analysis on the internal audit function in the Polish public administration.